Integrating Challenge-Based Learning in Arts and Design Research Classes - Glo, John Arvin (IJCAR: Indonesian Journal of Classroom Action Research, 2025)
This study explored the integration of challenge-based learning (CBL) in Arts and Design research classes. Pre-test and post-test assessments and a satisfaction survey were collected to determine its effectiveness with an average score of 23.15 to 28.27 out of 40 items showing an improvement in their research skills after the implementation. Satisfaction with CBL varied resulting in a mean score of 2.77 which corresponds that learners are satisfied with the intervention. These findings displayed that CBL can enhance research skills, especially in arts and design research classes. The data presented that the respondents improved their scores in the post-test. While in another survey, respondents were satisfied with the intervention of using CBL in their classes. This intervention is effective, as evidenced by improved test scores which determine the effectiveness of the used instructional methods. Improvements in some aspects of satisfaction can be made especially on the lecture quality, which suggests that future instructors must create more interactive and engaging research teaching methods to enhance learning outcomes and participant satisfaction. Therefore, this study displays how innovative instructional strategies and the importance of ongoing evaluation and refinement will ensure that educational practices meet learners' needs. The study concludes that CBL can be used by educators and policymakers to improve research education in arts and design research classes.